Combined testing of copeptin and high-sensitivity cardiac troponin T at presentation in comparison to other algorithms for rapid rule-out of acute myocardial infarction. (1st February 2019) - Mueller-Hennessen, Matthias; Lindahl, Bertil; Giannitsis, Evangelos; Vafaie, Mehrshad; Biener, Moritz; Haushofer, Alexander C.; Seier, Josef; Christ, Michael; Alquézar-Arbé, Aitor; deFilippi, Christopher R.; McCord, James; Body, Richard; et al.
Abstract: Background: We aimed to directly compare the diagnostic and prognostic performance of a dual maker strategy (DMS) with combined testing of copeptin and high-sensitivity (hs) cardiac troponin T (cTnT) at time of presentation with other algorithms for rapid rule-out of acute myocardial infarction (AMI). Methods: 922 patients presenting to the emergency department with suspected AMI and available baseline copeptin measurements qualified for the present TRAPID-AMI substudy. Diagnostic measures using the DMS (copeptin <10, <14 or < 20 pmol/L and hs-cTnT≤14 ng/L), the 1 h-algorithm (hs-cTnT<12 ng/L and change <3 ng/L at 1 h), as well as the hs-cTnT limit-of-blank (LoB, <3 ng/L) and -detection (LoD, <5 ng/L) were compared. Outcomes were assessed as combined end-points of death and myocardial re-infarction. Results: True-negative rule-out using the DMS could be achieved in 50.9%–62.3% of all patients compared to 35.0%, 45.3% and 64.5% using LoB, LoD or the 1 h-algorithm, respectively. The DMS showed NPVs of 98.1%–98.3% compared to 99.2% for the 1 h-algorithm, 99.4% for the LoB and 99.3% for the LoD. Sensitivities were 93.5%–94.8%, as well as 96.8%, 98.7% and 98.1%, respectively. Addition of clinical low-risk criteria such as a HEART-score ≤ 3 to the DMS resulted in NPVs and sensitivities of 100% with a true-negative rule-out to 33.8%–41.6%. Rates of the combined end-point of death/MI within 30 days ranged between 0.2% and 0.3% for all fast-rule-out protocols. Conclusion: Depending on the applied copeptin cut-off and addition of clinical low-risk criteria, the DMS might be an alternative to the hs-cTn-only-based algorithms for rapid AMI rule-out with comparable diagnostic measures and outcomes. Highlights: Combined testing of copeptin and high-sensitivity troponin T resulted in: Incremental clinical value to high-sensitivity troponin T alone at presentation Rule-out rates for myocardial infarction up to 62.3% in acute chest pain patients Negative predictive values >98% without and 100% with clinical low-risk criteria Similar diagnostic measures in comparison to other rapid rule-out algorithms Excellent prognosis for ruled-out patients in short- and long-term follow-up